Radiosonde measurements during POLARSTERN cruises (ANT-I/1 - PS109) - König-Langlo, Gert; Schmithüsen, Holger (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2025)
Since Polarstern's maiden cruise ANT-I/1 the meteorological observatory Polarstern continuously performs radiosoundings during times of ship operation. Typically, there is one launch to full altitude at 12 UTC every day. Additionally, there often is a launch with a smaller balloon for forecasting purposes (helicopter operations) around 6 UTC. All data reports are distributed via global networks of the World Meteorological Organisation. This data set contains all Polarstern radiosonde data sets until PS109. Beginning with PS110 the successor data set "Radiosonde measurements during POLARSTERN cruises (PS110 et seq), doi:10.1594/PANGAEA.974768" collects the respective data.
Keywords: Atmospheric soundings; Radiosonde; upper air profiles